Aerodynamic Analysis on Small Race Car Body by using CFD Simulation - Mohammad Rafi, Mohammad Syafiq (IRC, 2016)
Aerodynamic play the vital role in designing the car chassis or body frame. The airs seem to be the blind wall that exists during driving. The existence of the blind wall which the air resistance creates the investigation and research activities to overcome this situation with less negative effect during driving. Air resistance has tremendous effects on the way a car moving or accelerate and handling. Besides the application of the aerodynamic characteristic in order to increase the rate of acceleration, it also could contribute to the driving stability of the car. The goal of this project is to analyze the aerodynamic component of the UTP SAE small race car’s front nose and do some modification on the race car’s front nose design. In this project there will be two different type of front nose models which are basic design of UTP Formula SAE race car’s front nose and UTP Formula SAE race car’s front nose with additional spoiler. These two models of front nose was designed by using CATIA software and then will be evaluated based on aerodynamic components such as drag force, lift force and downforce. These two different model of race car’s front nose will undergoes aerodynamic analysis to observe the performance of modification by implementation of front spoiler.